KARAKTERISASI FILM KOMPOSIT ALGINAT DAN KITOSAN - Nur Rokhati; Bambang Pramudono; Nyoman Widiasa; Heru Susanto (Reaktor, 2012)
CHARACTERIZATION OF ALGINATE AND CHITOSAN COMPOSITE FILM. Due to the specific characteristics of (thin) films, the use of polymer films in various aplications has singnificantly increased. Alginate and chitosan are natural polymers, which have potential as a raw material for the manufacture of composite films. This paper presents the preparation and characterization of alginate, chitosan and chitosan-alginate composite films. The film characterization included permeability test, degree of swelling, mechanical property, morphology (by SEM), and surface chemistry (by FTIR). The results showed that alginate films have a higher permeability ​​and degree of swelling (DS) than chitosan films. Both permeability and DS decreased with increasing concentration for both alginate and chitosan films. DS experiments showed that the films have the highest DS in water followed by ethanol 95% and ethanol >99.9%, respectively. The mechanical strength of chitosan films was larger than alginate films. Alginate-chitosan composite films prepared by layer by layer method showed better characteristics than the composite films prepared by blending of alginate and chitosan solutions. Meningkatnya aplikasi film polimer di berbagai industri tidak terlepas dari keunggulan yang dimiliki. Alginat dan kitosan merupakan polimer alam yang mempunyai potensi sebagai bahan dasar pembuatan film komposit. Pada penelitian ini dilakukan pembuatan dan karakterisasi film komposit berbasis alginat dan kitosan. Karakterisasi film yang dilakukan meliputi uji: permeabilitas, derajat swelling, mekanik, morfologi (dengan SEM), dan struktur kimia permukaan (dengan FTIR). Hasil penelitian menunjukkan bahwa film alginat mempunyai nilai permeabilitas maupun derajat swelling yang lebih tinggi dibanding dengan film kitosan. Baik pada kitosan maupun alginat memberikan fenomena bahwa semakin besar konsentrasi larutan maka semakin kecil nilai permeabilitas maupun derajat swelling, dengan derajat swelling terhadap air adalah yang  paling besar kemudian diikuti oleh ethanol teknis (± 95%) dan yang terkecil adalah ethanol PA (> 99,9%). Kekuatan mekanik film kitosan lebih besar dibanding dengan film alginat. Film komposit alginat-kitosan yang dibuat dengan metode layer by layer memberikan karakteristik yang lebih baik dibanding dengan film komposit yang dibuat dengan pencampuran larutan alginat dan larutan kitosan.